Sensitive and direct electrochemical detection of double-stranded DNA utilizing alkaline phosphatase-labelled zinc finger proteins. Issue 12 (21st June 2015) - Noh, Soodong; Ha, Dat Thinh; Yang, Haesik; Kim, Moon-Soo
<x xml:space="preserve">Abstract</x> We report sensitive and direct detection of specific bacterial dsDNA sequences using (i) the zinc finger protein labelled with alkaline phosphatase and (ii) electrochemical measurement at the ITO electrode.